Arab Society: Demographic and Social Trends - Issue No. 16 - United Nations Economic; Social Commission for Western Asia (United Nations, 2023)
Arab Society: Demographic and Social Trends, Issue No. 16 is the latest in a series published biennially by the Statistics, Information Society and Technology Cluster of the Economic and Social Commission for Western Asia (ESCWA). Focusing on population dynamics, household composition, family formation, housing conditions, health, labour, poverty and inequality, education, culture and social participation, and the impact of the coronavirus disease (COVID-19) pandemic, the report provides a comprehensive and up-to-date overview of Arab society, showing how society is changing across countries in the ESCWA region and identifying a number of the factors that may be behind those trends. Data have been drawn primarily from the national statistical offices of ESCWA member States, supplemented by data from a wide range of international organizations. Arab Society: Demographic and Social Trends is produced with a wide audience in mind, including policy makers, service providers, researchers and teachers at academic institutions, journalists, staff at national statistical offices, and the public at large.